DIGITAL TWIN OF THE POSTGRADUATE EDUCATION INSTITUTION AS AN ECOSYSTEM OF PROFESSIONAL DEVELOPMENT - Tamara Sorochan; Lyubov Kartashova; Andrii Hurzhii (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article highlights new views on the possibilities of teachers' professional development in postgraduate education system, due to the transition from learning management systems (LMS) to the next generation digital learning environment (NGDLE) as an ecosystem of digital tools to support the activities of subjects of the educational process. For the first time, the authors have revealed the signs of environmental friendliness of the NGDLE, have characterized it as an open, stable, safe and comfortable system for subjects of the educational process, providing information exchange between them, as well as between them and the world around them. Such digital ecosystems are created as digital twins of the real postgraduate education institutions for the efficient lifelong learning and teachers' professional development. The practical implementation of these new generation concepts has been presented on the example of the Ukrainian Open University of Postgraduate Education, designed to organize and support non-formal postgraduate education. It has become a complex of digital solutions aimed at the implementation of EdTech with a priority in the successful functioning of virtual chairs, conducting the educational process (formal/non-formal education), professional development of students and teachers, attracting people from different regions of the country to training and teaching, highlighting innovative educational practice, etc.